Phospholipase A2 Receptor Antibody IgG4 Subclass Improves Sensitivity and Specificity in the Diagnosis of Idiopathic Membranous Nephropathy - Biao Huang; Yi Zhang; Liang Wang; Wenwei Xu; Jue Zhang; Qiuhua Zhang; Huiming Sheng; Zhigang Hu (Karger Publishers, 2019)
Aims: The aim of this study was to develop a new method for detecting anti-phospholipase A2 receptor-IgG4 to improve the sensitivity and specificity in the diagnosis of idiopathic membranous nephropathy (IMN). Methods: A highly sensitive quantitative assay was developed for the detection of serum anti-phospholipase A2 receptor-IgG4 with europium chelation by time-resolved fluoroimmunoassay (TRFIA), and a mouse anti-human IgG4 tracer was prepared using europium chelation for detection. The specificity and sensitivity of anti-phospholipase A2 receptor-IgG4 in the diagnosis of IMN were further assessed in patients with different kidney diseases. Results: The detection limit of anti-PLA2R-IgG4 was 0.69 ng/mL. The measurement range of anti-PLA2R-IgG4 TRFIA was 0.69-2,500 ng/mL. Mean serum anti-PLA2R-IgG4 was 21.27 ± 15.15 ng/mL in 45 healthy volunteers, 31.08 ± 18.17 ng/mL in 29 IgA nephropathy patients, 49.10 ± 34.32 ng/mL in 8 lupus nephropathy patients, and 10,324.11 ± 17,030.40 ng/mL in 30 IMN patients. The anti-PLA2R-IgG4 cutoff concentration was >161.2 ng/mL with the sensitivity of 90.0% and specificity of 100% in the diagnosis of IMN. However, the cutoff for other kidney diseases was lower than 161.2 ng/mL. Conclusion: The serum anti-phospholipase A2 receptor IgG4 detected with the method developed in this study has higher sensitivity and higher specificity than total IgG in the diagnosis of IMN.